Protective effects of blocking PD-1 pathway on retinal ganglion cells in a mouse model of chronic ocular hypertension - Sheng, Siqi; Ma, Yixian; Zou, Yue; Hu, Fangyuan; Chen, Ling (Frontiers in Immunology, 2023)
Purpose In this study, we aimed to investigate whether Programmed cell death 1 ligand 1/programmed cell death 1 ligand 2 (PD-L1/PD-L2) double knockout (dKO) has a protective effect on RGCs in a mouse model of chronic ocular hypertension (COHT). Methods We used superparamagnetic iron oxide to induce COHT in mice. Apoptosis of retinal ganglion cells (RGCs) and activation of microglia were evaluated using western blotting (WB) and immunofluorescence staining of the mouse retina. In addition, we also conducted transcriptome sequencing and further gene expression analyses using the gene ontology (GO) and Kyoto Encyclopedia of Genes (KEGG) database. Results In the mouse model of COHT, PD-L1/PD-L2 prevented the apoptosis of RGCs to some extent. Blocking the programmed cell death 1 (PD-1) pathway also increased the number of anti-inflammatory M2-activated microglia and enhanced the phosphorylation of its related pathway signal transducer and activator of transcription (STAT)6. Sequencing results showed that this protective effect may have been achieved by regulating the NF−B, tumour necrosis factor (TNF), PI3K/Akt and toll-like receptor signaling pathway etc. Conclusion Blocking the PD-1 pathway has a protective effect on RGCs in the mouse model of COHT induced by superparamagnetic iron oxide.